Allicin disrupts cardiac Cav1.2 channels via trafficking - Dan Han (Taylor & Francis Group, 2019)
Context: Allicin is a potential antiarrhythmic agent. The antiarrhythmic properties of allicin rely on its blockade of various cardiac ion channels. The l-type calcium (Cav1.2) channel provides a pivotal substrate for cardiac electrophysiologic activities. The mechanism of allicin on Cav1.2 remains unclear. Objective: This study evaluated the potential of allicin on the synthesis and trafficking of Cav1.2 channels. Materials and methods: Primary cardiomyocytes (CMs) from neonatal Sprague-Dawley (SD) rats were exposed to allicin (0, 0.0001, 0.001, 0.01, 0.1, 1, 10, 100 μg/mL) for 24 and 48 h. The CellTiter-Glo assay was performed to measure CM viability. Western blot with grayscale analysis and confocal laser scanning microscopy were used to evaluate the effects of allicin on the synthesis and trafficking of Cav1.2 channel proteins in primary CMs. Results: There was no significant difference in apoptotic toxicity from the actual cell viability (p > 0.05) in any group (0, 0.0001, 0.001, 0.01, 0.1, 1, 10, 100 μg/mL allicin), except that viability in the 0.001 and 0.01 μg/mL groups at 24 h were significantly greater (137.37 and 135.96%) (p < 0.05). Western blot with grayscale analysis revealed no substantial inhibition by allicin of the synthesis of Cav1.2 proteins. Confocal laser scanning microscopy revealed trafficking dysfunction of Cav1.2 channels caused by allicin in primary CMs. Conclusion: This study is the first to demonstrate that allicin inhibits cardiac Cav1.2 channels by disrupting trafficking, possibly mediating its antiarrhythmic benefits. Therefore, allicin might serve as a new antiarrhythmic agent in the future.